The role of lipids in the central nervous system and their pathological implications in amyotrophic lateral sclerosis. (April 2021) - Tracey, T.J.; Kirk, S.E.; Steyn, F.J.; Ngo, S.T.
Abstract: Lipids play an important role in the central nervous system (CNS). They contribute to the structural integrity and physical characteristics of cell and organelle membranes, act as bioactive signalling molecules, and are utilised as fuel sources for mitochondrial metabolism. The intricate homeostatic mechanisms underpinning lipid handling and metabolism across two major CNS cell types; neurons and astrocytes, are integral for cellular health and maintenance. Here, we explore the various roles of lipids in these two cell types. Given that changes in lipid metabolism have been identified in a number of neurodegenerative diseases, we also discuss changes in lipid handling and utilisation in the context of amyotrophic lateral sclerosis (ALS), in order to identify key cellular processes affected by the disease, and inform future areas of research.